A disease warranting attention from neurosurgeons: primary central nervous system post-transplant lymphoproliferative disorder - Jin, Lei; Lu, Di; Yan, Feng; Han, Jinkun; Wei, Penghu; Zhou, Yiqiang; Wang, Yaming; Shan, Yongzhi; Zhao, Guoguang (Frontiers in Neurology, 2024)
Background Primary central nervous system post-transplant lymphoproliferative disorder (PCNS-PTLD) is a rare condition, posing diagnostic and treatment challenges, with histological biopsy essential for diagnosis. Standardized treatment protocols are lacking. This disease requires urgent attention due to the increasing number of organ transplant surgeries and the use of immunosuppressive agents. Methods From 2020 to 2023, our center diagnosed five patients with PCNS-PTLD. We reviewed their clinical records and conducted a comprehensive analysis of 22 literatures on PCNS-PTLD cases following renal transplantation or allogeneic hematopoietic stem cell transplantation (HSCT). Results Four patients had previously received a kidney transplant, one had undergone allogeneic HSCT. The median time from the last transplant surgery to the diagnosis of PCNS-PTLD differs between kidney transplant (21.5 years) and allogeneic HSCT (9 months). Common symptoms included motor weakness (n = 4), headache (n = 2), confusion (n = 2), and nausea (n = 2), with ring-enhancing (n = 5), typically solitary (n = 3) and supratentorial (n = 3) lesions on imaging. Diagnosis involved robot-assisted stereotactic brain biopsy (n = 4) or craniotomy (n = 1), all showing Epstein-Barr virus and CD20 positivity. Most cases (n = 4) were monomorphic diffuse large B-cell lymphoma. Treatment included rituximab (n = 3), surgical resection (n = 2), zanubrutinib (n = 1), whole-brain radiation (n = 1), and methotrexate (n = 1). At the last follow-up, the median duration of follow-up for all patients was 19 months. During this time, 3 patients had died and 2 patients were still alive. Conclusion In patients with a history of kidney transplantation or allogeneic HSCT who are on long-term immunosuppressive therapy, any neurological symptoms, particularly the presence of supratentorial ring-enhancing masses in the brain on imaging, whether solitary or multiple, should raise high suspicion for this disease, warranting a timely brain biopsy. Additionally, we found that besides reducing immunosuppressants, zanubrutinib may be a potential, safe, and effective treatment for this condition. Moreover, post-surgical administration of rituximab in conjunction with whole-brain radiotherapy also appears to be a potentially safe and effective approach.